2018
DOI: 10.20944/preprints201808.0064.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymmetric Impacts of Oil Price on Inflation: An Empirical Study of African OPEC Member Countries

Abstract: This study investigates the asymmetric impacts of oil price changes on inflation in Algeria, Angola, Libya and Nigeria. Three different oil price data were applied in this study; the specific spot oil price of individual countries, the OPEC reference basket oil price and an average of the Brent, WTI and Dubai oil price. The dynamic panels ARDL were used to estimate the short and the long-run impacts. Also, this study partitioned the oil price into positive and negative changes to capture asymmetric impacts and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Higher oil prices impact the economy in a number of ways: transfer of income from oil importing economies to oil exporters; rise in the cost of production of goods and services in an economy emanating from an upsurge in the relative price of energy inputs; it impacts on the price level; decline in economy's productive capacity as producers respond to higher oil prices by reducing their utilization of both oil and capital; and uncertainty in investment decisions by households and firms owing to uncertain oil prices in the future. Others include direct and indirect impacts on financial markets and the incentive for providers of energy to increase production and investment (Fried & Schultze, 1975;Marquez, 1986;Blanchard & Gali, 2007;DePratto et al, 2009;Bataa, 2010;Alvarez et al, 2011;Trang et al, 2017;Bala & Chin, 2018). The magnitude and direction of its impact, however, differ between industrial and developing countries as well as between oil producing and consuming economies (IMF, 2000).…”
Section: Theoretical Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Higher oil prices impact the economy in a number of ways: transfer of income from oil importing economies to oil exporters; rise in the cost of production of goods and services in an economy emanating from an upsurge in the relative price of energy inputs; it impacts on the price level; decline in economy's productive capacity as producers respond to higher oil prices by reducing their utilization of both oil and capital; and uncertainty in investment decisions by households and firms owing to uncertain oil prices in the future. Others include direct and indirect impacts on financial markets and the incentive for providers of energy to increase production and investment (Fried & Schultze, 1975;Marquez, 1986;Blanchard & Gali, 2007;DePratto et al, 2009;Bataa, 2010;Alvarez et al, 2011;Trang et al, 2017;Bala & Chin, 2018). The magnitude and direction of its impact, however, differ between industrial and developing countries as well as between oil producing and consuming economies (IMF, 2000).…”
Section: Theoretical Literaturementioning
confidence: 99%
“…The study found, among others, that oil price hikes induced a 43 percent increase in inflation in a year, while a fall in oil prices leads to a 29 percent increase in inflation. Bala and Chin (2018) estimates the asymmetric impacts of oil price shocks on inflation in four African oil producing countries -Algeria, Angola, Libya and Nigeria using the ARDL dynamic panels framework. The study discovered that both positive and negative oil price shocks positively influence inflation in these countries during the period, but the impact was more pronounced in periods of oil price declines.…”
Section: -113mentioning
confidence: 99%
See 2 more Smart Citations
“…The study concluded that an oil price shock causes inflation index to rise while oil price uncertainty has no effect on the increase in inflation. Bala & Chin (2018) investigated the asymmetric effect of oil price shocks on inflation in small oil exporting economies like Nigeria, Libya, Algeria and Angola. Utilising the NARDL dynamic panels, they observed that both the positive and negative oil price changes affected the level of inflation.…”
Section: Article In Press -Corrected Proofmentioning
confidence: 99%